Current Status and New Challenges of The Tunka Radio Extension. (February 2019) - Lenok, V.; Bezyazeekov, P.A.; Budnev, N.M.; Chernykh, D.; Fedorov, O.; Gress, O.A.; Haungs, A.; Hiller, R.; Huege, T.; Kazarina, Y.; Kleifges, M.; Kostunin, D.; et al.
Abstract: The Tunka Radio Extension (Tunka-Rex) is an antenna array spread over an area of about 1 km 2 . The array is placed at the Tunka Advanced Instrument for cosmic rays and Gamma Astronomy (TAIGA) and detects the radio emission of air showers in the band of 30 to 80 MHz. During the last years it was shown that a sparse array such as Tunka-Rex is capable of reconstructing the parameters of the primary particle as accurate as the modern instruments. Based on these results we continue developing our data analysis. Our next goal is the reconstruction of cosmic-ray energy spectrum observed only by a radio instrument. Taking a step towards it, we develop a model of aperture of our instrument and test it against hybrid TAIGA observations and Monte-Carlo simulations. In the present work we give an overview of the current status and results for the last five years of operation of Tunka-Rex and discuss prospects of the cosmic-ray energy estimation with sparse radio arrays.